Bahasa Inggris - Rahmadi Agus Setiawan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
The construction sector in Indonesia faces an ethical crisis spanning structural failures that endanger life, pervasive corruption, and ecological degradation, problems that are fundamentally moral rather than merely technical. Islamic Religious Education (PAI) in public universities is institutionally positioned to address this crisis, yet in engineering faculties it remains normative-textual and epistemologically isolated from students' technical disciplines. This study aims to reconstruct an integrated PAI-STEAM curriculum for civil engineering programs by operationalizing the maqāshid al-sharīʿa as an ethics of infrastructure engineering aligned with global accreditation standards. Employing qualitative library research with a philosophical-hermeneutic approach, the study analyzes Islamic juridical sources and engineering-accreditation documents through transdisciplinary content analysis and creative synthesis. The study yields three principal results. First, integration requires dissolving the dichotomy of knowledge at the epistemological level, repositioning engineering laws as sunnat Allāh and the STEAM